Gagasan Instagram Mubadalah.id dalam Mewujudkan Islam Moderat di Indonesia - Eko Zulfikar; Apriyanti Apriyanti; Halimatussa'diyah Halimatussa'diyah (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
The phenomenon of radicalism in Indonesia goes on because of conflict and social friction among religious people. One of the reasons for this potential conflict is the development of information technology which makes it easier for internet users to disseminate the news they receive. On the contrary social media can also promote religious moderation ideas. Religious moderation protects religious people from going to extremes in insulting religious teachings which results in disunity. This article aims to find out the idea of the Mubadalah.id account in strengthening religious moderation, at the same time realizing moderate Islam in Indonesia. By using virtual ethnographic methods and content analysis techniques, this paper concludes that the Mubadalah.id account has carried the significant ideas as an effort to realize moderate Islam in Indonesia based on the four indicators of religious moderation of the Indonesian Ministry of Religion, namely: (1) promoting peaceful and tolerant religious principles; (2) upholding human values through gender equality; (3) voice for State Defense; (4) defending human rights, especially for women and children who are oppressed; and (5) strive for environmental preservation.